Research on optimization of green marine fuel supply chain considering fuel substitution effects - Jiang, Yanchao; Xu, Chang-yan; Xu, Jihong (Frontiers in Marine Science, 2025)
The adoption of green fuels in the shipping industry serves as a primary means to reduce carbon emissions. However, its widespread implementation faces coordination challenges among government, port, and marine fuel supplier. This paper develops a marine fuel supply chain model comprising government, port, marine green and conventional fuel suppliers, comparatively analyzing the decision-making effects of various entities in the marine fuel supply chain under non-cooperative fuel suppliers without government participation, cooperative fuel suppliers without government participation, non-cooperative fuel suppliers with government participation, and cooperative fuel suppliers with government participation four different models. The paper primarily examines key performance indicators including government expenditure, port profit, and the aggregate profits of the two marine fuel suppliers. The findings demonstrate that: carbon tax can effectively boost the sales of green marine fuel, marine fuel suppliers collaboration significantly reduces government expenditure; and increased substitutability between green and conventional marine fuels leads to rising trends in government expenditure, port profit, and total marine fuel supplier profit.